2011
DOI: 10.5171/2011.141651
|View full text |Cite
|
Sign up to set email alerts
|

Identifying User Requirements of Mobile Government Services in Malaysia Using Focus Group Methodch

Abstract: Mobile government implementation in Malaysia is still in its very early stages -indeed a comprehensive m-Government has not been shaped yet. In this regard, we need to investigate the potential needs of users of m-Government services. In addition, there is a need to describe the factors that lead to the integration of the services provided with users' everyday practices. In this research, we examined different groups of citizens with varying needs and practices in the available technologies. Focus groups metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Users of m-Government services might be disappointed if they cannot obtain the information they need in a short period of time. This has been supported by a number of studies (Abu-Samaha & Samad, 2008;Al-Thunibat et al, 2011;Ghyasi & Kushchu, 2004;El-Kiki & Lawrence, 2006;Al-Khamayseh et al, 2007;Sheng & Trimi, 2008;Salkute et al, 2011;Shareef et al, 2016). Karan & Khoo, 2008;Kumar & Sinha, 2007;Salkute et al, 2011;Sandy & McMillan, 2005;Sareen et al, 2013;Sheng & Trimi, 2008).…”
Section: Usabilitymentioning
confidence: 77%
See 2 more Smart Citations
“…Users of m-Government services might be disappointed if they cannot obtain the information they need in a short period of time. This has been supported by a number of studies (Abu-Samaha & Samad, 2008;Al-Thunibat et al, 2011;Ghyasi & Kushchu, 2004;El-Kiki & Lawrence, 2006;Al-Khamayseh et al, 2007;Sheng & Trimi, 2008;Salkute et al, 2011;Shareef et al, 2016). Karan & Khoo, 2008;Kumar & Sinha, 2007;Salkute et al, 2011;Sandy & McMillan, 2005;Sareen et al, 2013;Sheng & Trimi, 2008).…”
Section: Usabilitymentioning
confidence: 77%
“…Usually, individuals with strong positive initiatives and characteristics are likely to try new technologies; thus, it is reasonable to expect them to have positive intentions to use mobile services. Studies have suggested that, in designing m-Government services, attention should not only be given to the technology and from the government's perspective but also from users' characteristics (Al-Khamayseh et al, 2007;Alssbaiheen & Love, 2015;Al-Thunibat et al, 2011 andGhyasi &Kushchu, 2004). A robust analysis of the system is needed in order to ensure that the needs of all users are met and to ensure that both the functional and nonfunctional requirements of the mobile applications are given sufficient attention to meet users' needs (Ivan & Zamfiroiu, 2011).…”
Section: Personal Initiatives and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Thunibat, Zin, and Sahari (2011) use this aforementioned technique to identify user requirements of mobile government services, Klein, Tellefsen, and Herskovitz (2007) highlight and analyze the focus groups supported by information technology (e.g. group support systems) to finalize the qualitative research, Sein, Henfridsson, Purao, Rossi, and Lindgren (2011) adopt focus group method to investigate the application of competence management in the proposed action design research, and Smith, Sosa, Tisone, and Mckyer (2011) conduct an instrument development in health research to increase the quality and validity of measurement based on focus group method.…”
Section: Methodology-focus Group Methodsmentioning
confidence: 98%
“…Maumbe and Owei (2006) examined major factors affecting m-government use by citizens, business and government; and it highlights implementation challenges and provided a framework for m-government deployment in South Africa. Al Thunibat et al (2011) carried out a study on mobile government implementation in Malaysia and investigated the potential needs of users of m-government services. The results of the study indicated that although awareness of mobile government services is reasonably high, only a small number of Malaysians actually use mobile government services due to security, cost, quality of services, access speed, interface design and information updating issues.…”
Section: Literature Reviewmentioning
confidence: 99%